Using Next Generation Sequencing to Study the Genetic Diversity of Candidate Live Attenuated Zika Vaccines - Natalie D. Collins (Vaccines, 2020)
Zika virus (ZIKV) is a mosquito-transmitted positive-sense RNA virus in the family Flaviviridae. Candidate live-attenuated vaccine (LAV) viruses with engineered deletions in the 3’ untranslated region (UTR) provide immunity and protection in animal models of ZIKV infection, and phenotypic studies show that LAVs retain protective abilities following in vitro passage. The present study investigated the genetic diversity of wild-type (WT) parent ZIKV and its candidate LAVs using next generation sequencing analysis of five sequential in vitro passages. The results show that genomic entropy of WT ZIKV steadily increases during in vitro passage, whereas that of LAVs also increased by passage number five but was variable throughout passaging. Additionally, clusters of single nucleotide variants (SNVs) were found to be present in the pre-membrane/membrane (prM), envelope (E), nonstructural protein NS1 (NS1), and other nonstructural protein genes, depending on the specific deletion, whereas in the parent WT ZIKV, they are more abundant in prM and NS1. Ultimately, both the parental WT and LAV derivatives increase in genetic diversity, with evidence of adaptation following passage.